2008
DOI: 10.1039/b805658g
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured thin solid oxide fuel cells with high power density

Abstract: Nanostructured thin film solid oxide fuel cells (SOFC) have been developed for reduced temperature operation, with high power density, and to be self reforming. A thin film electrolyte (1-2 microm thickness), e.g., yttria-stabilized zirconia (YSZ), is deposited on a nickel foil substrate. The electrolyte thin film is polycrystalline when deposited on a polycrystalline nickel foil substrate, and is (100) textured when deposited on an atomically textured nickel foil substrate. The Ni foil substrate is then conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 14 publications
(8 reference statements)
0
39
1
Order By: Relevance
“…Especially, the latter is an important task for cutting down the burden in the thermal management of an integrated power pack, as well as for improving the reliability of the cell and the stack by preventing reaction between components. Although cutting down the Ohmic resistance by using thin film electrolytes is the most commonly sought approach to lower the operating temperature of SOFCs [1,[3][4][5][6], reducing polarisation losses at the lower temperature range is still a significant issue to be solved [7]. Therefore, cathode materials with high mixed ionic and electronic conducting (MIEC) properties like lanthanum strontium cobalt oxide (LSC) and other cobalt containing cathodes were studied for the lower temperature operation of SOFCs [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, the latter is an important task for cutting down the burden in the thermal management of an integrated power pack, as well as for improving the reliability of the cell and the stack by preventing reaction between components. Although cutting down the Ohmic resistance by using thin film electrolytes is the most commonly sought approach to lower the operating temperature of SOFCs [1,[3][4][5][6], reducing polarisation losses at the lower temperature range is still a significant issue to be solved [7]. Therefore, cathode materials with high mixed ionic and electronic conducting (MIEC) properties like lanthanum strontium cobalt oxide (LSC) and other cobalt containing cathodes were studied for the lower temperature operation of SOFCs [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there have been many efforts to apply Co-containing cathode materials directly over YSZ with thin film deposition techniques which can prevent the cathode/electrolyte combination from being exposed to high temperatures [9][10][11][12][13][14][15]. Especially in the field of the micro-SOFC research with thin film components, cells have been fabricated by directly applying Co-containing cathodes to the YSZ electrolyte because it is expected that the interfacial reaction would not occur at low temperatures [4,16,17]. Recently, however, concerns have arisen that the reaction actually occurs at much lower temperatures (∼700°C) than expected when nano-structured thin film cathodes were applied [7,10,13].…”
Section: Introductionmentioning
confidence: 99%
“…There are two problems between the Co-containing cathode and the YSZ electrolyte: high chemical reactivity (at T P 900°C) and thermal expansion coefficient mismatch [15]. There are many efforts on directly depositing Co-containing cathode on YSZ electrolyte and these methods are performed at low temperatures [16][17][18]. However, Noh et al [1] have reported that even though the processing temperatures were strictly controlled lower than 650°C, the La 0.6 Sr 0.4 CoO 3Àd cathode still reacted with the YSZ electrolyte when they directly contacted with each other.…”
Section: Introductionmentioning
confidence: 99%
“…Decreasing the operational temperature decreases the YSZ ionic conductivity, but this can be compensated by reducing the thickness of the electrolyte, and thus reducing ohmic losses 4,[6][7][8][9][10][11][12] . Thin and dense YSZ electrolytes can be fabricated by different techniques such as physical or chemical vapor deposition (PVD, CVD), plasma enhanced CVD (PECVD), sol-gel method, electrochemical vapor deposition, suspension or atmospheric plasma spraying [13][14] , pulsed laser deposition (PLD) 15 , etc.…”
Section: Introductionmentioning
confidence: 99%
“…The YSZ is a standard electrolyte for SOFCs, which are potential candidates for next generation portable and mobile power sources [3][4][5][6][7][8][9][10] . Standard YSZ electrolytes operate at high temperatures (800-1000 °C) due to their ionic conductivity properties which become efficient enough only at this temperature range.…”
Section: Introductionmentioning
confidence: 99%